Preservation of Yoruba Indigenous Drumming Heritage - Olusegun Adebolu Oladosu (Yoruba Studies Review)
The cultural and religious experiences and expressions of the Yorùbá people are mediums to their ways of life. Culture as defined is “a way of life” with both tangible and intangible elements embedded in the culture. The behavior, beliefs, values, and symbols that the Yorùbá accept are represented through culture. The indigenous drum, as part of the tangible aspects of Yorùbá culture from the past, has been one of the mediums of displaying their cultural heritage; and therefore instituting models of socialization. Despite the importance of the heritage, it shows that modernization and civilization have brought different reflections on the nature of Yorùbá drumming and this in a way reduces the cultural values of the drumming performance. This paper tends to look at the values of indigenous drum among the Yorùbá people through the phenomenological framework and then show how its lost glory can be revived in action and written forms. The submission of the paper is to emphasize that indigenous drumming orality amidst these challenges can still cope with modern influence.